2009
DOI: 10.1007/s12550-009-0033-z
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic effect of fumonisin B1 and ochratoxin A on human and pig lymphocytes using the Methyl Thiazol Tetrazolium (MTT) assay

Abstract: Lymphocytes cell obtained from healthy human donors and pigs were exposed to fumonisin B1 (FB1) and ochratoxin A (OTA), which have been found to be immunosuppressive, carcinogenic and mutagenic, to ascertain their single and combined cytotoxic effects with time and to assess the suitability of animal lymphocytes as test agents in comparison to human cells. The main objectives of this work were to assess the use of animal lymphocytes, particularly pig lymphocytes, for their use in the Methyl Thiazol Tetrazolium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Moreover, synergistic effects on both liver and kidneys were observed after the ingestion of feed by rabbits contaminatedwithAFB 1 and FB 1 (Orsi et al, 2007). Furthermore, several in vitro investigations conducted on different human and pig cell lines seem to have confirmed an increase in cytotoxicity associated with the simultaneous presence of OTA and FB 1 (Creppy et al, 2004;Mwanza et al, 2009).…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, synergistic effects on both liver and kidneys were observed after the ingestion of feed by rabbits contaminatedwithAFB 1 and FB 1 (Orsi et al, 2007). Furthermore, several in vitro investigations conducted on different human and pig cell lines seem to have confirmed an increase in cytotoxicity associated with the simultaneous presence of OTA and FB 1 (Creppy et al, 2004;Mwanza et al, 2009).…”
Section: Discussionmentioning
confidence: 89%
“…During the last decades, the Scientific Committee on Food from the European Food Safety Authority (EFSA; Directorate General for Consumers) has expressed scientific opinions on some commonly occurring Fusarium toxins, their occurrence in food and assessment of dietary intakes by the population of European Union (EU) member states and are publically available (http://ec.europa.eu/food/food/chemicalsafety/contaminants/fusarium_en.htm) (EFSA, 2008). Although there are several studies on the combined effects of mycotoxins (Boeira et al, 2000;Kebena et al, 1997;Klarić et al, 2008;Kouadio et al, 2007;Luongo et al, 2008Luongo et al, , 2006McKean et al, 2006;Mwanza et al, 2009;Ruiz et al, 2011), the nature of combined effect or the relative potencies of the mycotoxins are still not fully understood. Fusarium toxins are a chemically diverse group of compounds, which can elicit a wide range of toxicological responses (Coulombe, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The Methyl Thiazol Tetrazolium (MTT) assay is one of the most commonly used in vitro method for preliminary screening since developed (Mosmann, 1983). It determines the ability of living cells to convert a soluble yellow tetrazolium salt [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] into insoluble purple formazan crystals by catalytic action of mitochondrial succinyl dehydrogenase enzymes (Cetin and Bullerman, 2005;Mwanza et al, 2009;Slater et al, 1963). The purple precipitates formed can then be dissolved in dimethylsulphoxide (Hanelt et al, 1994), sodium dodecyl sulphate (Meky et al, 2001) or acid isopropanol (Mosmann, 1983) to give coloured solution, which can be measured spectrophotometrically.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pig nutrition is based on cereals, which can contain considerable amount of mycotoxins, so besides poultry, pigs are the most frequently exposed farm animals. In a previous study, we found pig lymphocytes to be more sensitive to the cytotoxic effect of mycotoxins than human lymphocytes (Mwanza et al, 2009). Thus, using the lymphocytes of the same genotype, sex and age may provide homogeneous cells for the study, supporting the reproducibility of the test.…”
Section: Acta Veterinaria Hungarica 61 2013mentioning
confidence: 58%